Hope and Responsibility Vested in Younger Generations: the Case of Hungary - Zsuzsanna Marton; Ildikó Ernszt; Nóra Rodek; Tivadar Máhr (Interdisciplinary Description of Complex Systems, 2020)
In the era of consumer society, the depletion of the world’s natural resources brings conscious consumption in the spotlight. More and more people are said to be conscious consumers, who act responsibly with regard to the environment and society. Therefore, researches about conscious and responsible purchase behaviour draw the attention of economists and marketing specialists as well – thus being able to form their market actions. According to the stereotype about conscious consumers in our heads, the conscious consumer is young, well educated, and female. This paper aims to reveal the consumption habits of people and their attitude toward consciousness and responsibility, furthermore, to investigate them from the stereotype’s point of view that finds youngsters more conscious. An online survey was conducted with 652 consumers of a German supermarket chain in Hungary. The research concentrates on identifying the main differences between generations regarding their purchase habits. The research results show that the consciousness is rather manifested in the self-interest than in the responsibility. While other international survey data have proven development through generations and found younger consumers more conscious and responsible, this fact has not been statistically proven in Hungary. The real causes or drivers behind conscious behaviour are still questionable in the Hungarian market.